Análisis de las políticas públicas y su repercusión en el comercio informal de los mercados en el cantón santo domingo, año 2023 - Ronquillo Molina , Kevin Javier (2025)
Public policies seek to improve citizens' living conditions by addressing their needs through the creation of norms, laws, and programs. Public policies play a key role in regulating informal trade in the markets of the Decentralized Autonomous Municipal Government (GADM), specifically in the case of the Santo Domingo de los Tsáchilas canton. To achieve this general objective, the research aims to identify the current status of these policies, investigating their effectiveness, level of awareness, and participation of informal merchants in their implementation. This research uses tools such as interviews and surveys among merchants and local authorities. It also seeks to deduce the factors that influence awareness of informal trade in the canton. Finally, the development of a plan to improve public policies targeting informal trade is proposed. This plan establishes strategies for the effective dissemination of existing policies, the simplification of administrative documents, and the improvement of municipal market infrastructure. The results show that the majority of respondents are unaware of the existence of public policies regulating informal trade. Merchants also indicate that they lack sufficient information about the formality of trade, are dissatisfied with the availability of adequate spaces and the effectiveness of the measures implemented, and lastly, limited participation in training and workshops. Finally, several factors were identified as barriers to legalizing the economy.